Sympoiesis, Autopoiesis and Immunity: How to Coexist with Nonhuman Others? - Žukauskaitė, Audronė (Text Matters: A Journal of Literature, Theory and Culture, 2022)
In this essay I will discuss Donna J. Haraway’s notion of sympoiesis and examine different modes of cohabitation or hybridization with nonhuman others. Such concepts as sympoiesis, or holobiont, question the notion of the biological individual and also change our understanding of what it means to be human. As Richard Grusin pointed out, “we have never been human” because “the human has always coevolved, coexisted, or collaborated with the nonhuman—and that the human is characterized precisely by this indistinction from the nonhuman” (ix–x). We have never been human because we have always been dependent on other species living within or beyond our bodies. However, the question which still needs to be answered is whether all forms of coexistence are profitable and welcomed. How does one define the limit at which this co-existence is collaborative and productive (“posthuman”), and beyond which it becomes damaging and lethal (in other words, “posthumous,” e.g., coming after life)? For this reason, the interrelations between different life forms should be discussed together with the concepts of contagion and immunity. The notion of immunity expresses an ambivalent character of life: on the one hand, it protects the organism against everything that is beyond its boundary; on the other hand, it helps to collaborate with other organisms and to create an ecosystem. In this sense, immunity can be thought as a field of negotiations between human and nonhuman beings.